Sommelier craft : Aesthetic judgements in the performance of decanting - Scander, Henrik (FormAkademisk, 2023)
This performance study focuses on sommeliers, delving into what constitutes their work and the process of achieving this title. Sommeliers are wine specialists tasked with the responsibility of ensuring that beverages are served properly in combination with food. Similar to other craft persons, the sommelier’s craft is connected to their knowledge of the products, primarily wine and other beverages, and the products’ relation to different foods. The art of tasting is an acquired knowledge, an embodied craft, a central professional competence to determine the quality of beverages. Other elements of sommelier knowledge are communication with guests, a social craft, and how to move in relation to the room, a spatial craft, both of which are based on the influence of different contexts. This study highlights the complexity of aesthetic judgements that sommeliers make through their embodied, social and spatial craft practices while decanting wine and serving it to a guest. It uses a video-reflexive ethnography to emphasise the aesthetics of the sommelier craft. The decanting is carried out in line with the guidelines of the International Sommelier Association. Simultaneously, some judgements in the performance must be articulated verbally to emphasise the complexity of the different crafts in relation to the importance of understanding the complexity in adopting the service to the situation. Social, embodied and spatial craft practices, in relation to the sommelier, show how aesthetic judgements are developed into a willingness to understand people and satisfy guests. This is achieved by 'cognitive planning’, which entails working diligently and preparing to enhance the efficiency of the craft, and by ‘situational adjustments’ that occur in real time to improve and optimise the guest's experience.